2022
DOI: 10.3390/genes13030474
|View full text |Cite
|
Sign up to set email alerts
|

Division of Labor by the HELQ, BLM, and FANCM Helicases during Homologous Recombination Repair in Drosophila melanogaster

Abstract: Repair of DNA double-strand breaks by homologous recombination (HR) requires a carefully orchestrated sequence of events involving many proteins. One type of HR, synthesis-dependent strand annealing (SDSA), proceeds via the formation of a displacement loop (D-loop) when RAD51-coated single-stranded DNA invades a homologous template. The 3′ end of the single-stranded DNA is extended by DNA synthesis. In SDSA, the D-loop is then disassembled prior to strand annealing. While many helicases can unwind D-loops in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…DNA synthesis extension of the 3’ end ensures replication through the gapped region, and upon re-annealing to the parental strand of the original chromatid, the gap is filled. HELQ activity may also be required at this stage (in addition to or instead of the 3’ end unwinding), since previous studies have shown that HELQ participates in 3’ end extension downstream of D-loop formation, potentially through removing RAD51 from the dsDNA formed at the D-loop, and thus allowing for DNA polymerase engagement (Adelman et al, 2013; Thomas et al, 2022; Ward et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA synthesis extension of the 3’ end ensures replication through the gapped region, and upon re-annealing to the parental strand of the original chromatid, the gap is filled. HELQ activity may also be required at this stage (in addition to or instead of the 3’ end unwinding), since previous studies have shown that HELQ participates in 3’ end extension downstream of D-loop formation, potentially through removing RAD51 from the dsDNA formed at the D-loop, and thus allowing for DNA polymerase engagement (Adelman et al, 2013; Thomas et al, 2022; Ward et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the 3' end formed on the parental strand could invade the sister chromatid allowing repair from this template. Loss of HELQ may interfere with this process, since HELQ was shown to participate in D-loop extension as mentioned above (Adelman et al, 2013;Thomas et al, 2022;Ward et al, 2010). Thus, HELQ-depleted PRIMPOL-overexpressing cells not only accumulate ssDNA gaps due to defective gap filling, but also, upon MRE11-mediated conversion of these gaps into DSBs, are unable to repair these breaks since a critical step in the HR mechanism is compromised.…”
mentioning
confidence: 99%
“…Kras signaling is negatively associated with HELQ expression in patients with CLL, and ulixertinib, a Kras signaling inhibitor, may offer a new therapeutic option for patients with HELQ-low CLL (88,91). Furthermore, topotecan, a topoisomerase I inhibitor, is sensitive in HELQ mutants that induce single-ended DNA DSBs in replicating cells (92). In additionally, a RAD51 inhibitor, Cam833, which disrupts the interaction between RAD51 and BRCA2, synergizes with the poly (ADP-ribose) polymerase (PARP) inhibitors (93).…”
Section: Pan-cancer Analysis Of Helqmentioning
confidence: 99%
“…It contributes to DNA break repair in metazoans but is absent from yeasts. Loss of HelQ ( HELQ − / − ) in cells predisposes to cancers and infertility ( 24–27 ) and corresponds to increased frequencies of tandem DNA duplications and long-tracts of DNA repair synthesis during homologous recombination ( 28 , 29 ) and reduced repair by synthesis-dependent strand annealing (SDSA) ( 30 ). HelQ also promotes DNA strand annealing in contexts distinct from MMEJ-like DNA repair by its homologue PolQ, a polymerase-helicase that is also found only in metazoans ( 28 ).…”
Section: Introductionmentioning
confidence: 99%